Monday
March 27, 2017

Post a New Question

Posted by on .

solve for u, u=sqrt -u+6

u=ã-u+6

  • algebra - ,

    do you mean

    u = (sqrt(-6 + u))

    please use the word 'sqrt' and put in ()
    what is included under the radical

    we will be able to assist you much faster if what you need is more clear

    thank you

  • algebra - ,

    u = (sqrt(-u + 6))

    u = (sqrt(6 - u))
    square both sides
    u^2 = 6 - u
    u^2 + u - 6

    complete the square
    u^2 + u = 6
    u^2 + u + 1/4 = 6 + 1/4
    (u + 1/2)^2 = 25/4
    take the square root of both sides

    + - (u + 1/2) = 5/2
    u + 1/2 = 5/2
    u = 4/2 = 2

    -u - 1/2 = 5/2
    -u = 6/2 = 3
    u = -3

    check for u = 2
    u = (sqrt(6 - u))
    2 = (sqrt(6 - 2))
    2 = sqrt 4
    2 = 2

    check for u = -3
    u = (sqrt(6 - u))
    -3 = (sqrt(6 + 3))
    -3 = sqrt 9
    -3 not = 3

    so, the only solution is u = 2

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question